2015
DOI: 10.1042/bsr20150151
|View full text |Cite
|
Sign up to set email alerts
|

FOXL2 down-regulates vitellogenin expression at mature stage in Eriocheir sinensis

Abstract: The present study highlights that forkhead transcription factor (FOXL)2 down-regulates vitellogenin (VTG) synthesis not only through the regulation of follicular cell apoptosis with DEAD-box RNA helicase 20 (DDX20), but also may through the steroidogenic pathway with fushi tarazu factor (FTZ-F)1 at mature stage in Eriocheir sinensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Interestingly, the expression level of foxl2 was increased slightly, rather than decreased, in the knockdown ovary and testis comparing to that of the control group. In most species, foxl2 is predominantly expressed in ovarian granulosa cells and is required for ovary differentiation and maintenance [36,37,38,39,40]. Recently, it has been reported that the foxl2 transcript is expressed in both the ovary and testis of M. nudus [19].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression level of foxl2 was increased slightly, rather than decreased, in the knockdown ovary and testis comparing to that of the control group. In most species, foxl2 is predominantly expressed in ovarian granulosa cells and is required for ovary differentiation and maintenance [36,37,38,39,40]. Recently, it has been reported that the foxl2 transcript is expressed in both the ovary and testis of M. nudus [19].…”
Section: Discussionmentioning
confidence: 99%
“…FOXL2 negatively regulates the VTG synthesis at developmental stage. FOXL2 downregulates VTG's expression by binding DDX20 in the regulation of follicular cell apoptosis and repress the synthesis of VTG when bound with FTZ-F1 at the mature stage [ 18 , 34 , 35 ]. According to our research, during the process of testis development, FOXL2 had no obvious change, and FTZ-F1 gene was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…1 , table 1 ), including sponges (Suberites domuncula) [Adell and Müller, 2004], mollusks [Naimi et al, 2009;Teaniniuraitemoana et al, 2014;Zhang et al, 2014;Tong et al, 2015], arthropods including insects and crustaceans [De Loof et al, 2010;Ma et al, 2012;Farlora et al, 2014;Li et al, 2015], hemichordates [Fritzenwanker et al, . See text for details.…”
Section: The Complexity Of Foxl2 Gene Evolutionmentioning
confidence: 99%